Three-layer structure of the Carpathian sedimentary prism from the results of seismic migration on the PANCAKE and RomUkrSeis WARR profiles - Т.П. Єгорова; О.О. Верпаховська; Ґ.В. Муровська (Геофизический журнал, 2022)
The method of finite-difference migration of reflected/refracted waves, applied to the PANCAKE and RomUkrSeis WARR seismic profiles, made it possible to form wave images of sedimentary layer and crystalline basement under the Carpathian orogen to a depth of 25 km. The study area belongs to Ukrainian Carpathians, which consist of Outer Carpathians — the Cretaceous-Neogene accretionary prism and Inner Carpathians —fragments of Alkapa and Tissia-Dakia microplates. The Carpathian belt is thrusted over the Neogene Carpathian Foredeep, which was laid on the basement of the Eastern/West European platforms. We used a technique specially developed for WARR study to generate a wave image of basement and deep sedimentary basin. The wave images obtained for two profiles show the presence of deep troughs (accretionary prism) under the Carpathian orogen and reveal their similarities and differences due to the peculiarities of the tectonic development in the junction zone of East- and West European platforms. The sedimentary prism reaches a depth of 20 km and consists of three nested troughs distinguished well in the wave field and characterized by different velocities on velocity models. The upper two layers up to ~15 km belong to the allochthon of the Ukrainian Carpathians and the underlying sequence. Whereas the lower one (15—21 km) could represent the older complexes of the basement, up to the Neoproterozoic age (Ediacaran), associated with accretion of young plates from the west to the East European platform and formation of the Trans-European suture zone. The deep trough along the RomUkrSeis profile is significantly narrower than along the PANCAKE one, which indicates a stronger shortening of the sedimentary basin (and possibly the upper crust) in the southeastern part of Ukrainian Carpathians. The sedimentary prism on both profiles is bounded from both sides by steeply dipping faults — from the east by the Forecarpathian fault, and from the west by the Transcarpathian fault along PANCAKE profile and by the Dragos Voda fault on RomUkrSeis profile, which may indicate active strike-slip tectonics.